Modalism in some Brazilian post-Bossa Nova composers of the 1960s (Per Musi, 2014)
Study about the use of modalism in Brazilian popular music of the post Bossa Nova era in the 1960s. The emphasis on popular culture via canção de protesto (the Brazilian protest song) reveals the common usage of modal procedures in several representative composers of that time (Luiz Gonzaga, Jackson do Pandeiro, Edu Lobo, Geraldo Vandré, Baden Powell, Vinicius de Moraes, Moacir Santos, Egberto Gismonti, Milton Nascimento e Caetano Veloso). The occurrence of these procedures is based in comparisons with manifestations of US modal jazz as well as ethnic music traditions of Brazil, which guided an aesthetic trend of that period.